Formulasi serum antiaging nanopartikel emas dengan fraksi daun sirih hutan gambut Kalimantan (Piper aduncum) - Gerung, Jenny Blessia; Sulistia, Tiya; Yulita, Elia; Sametri, Ni Wayan Septia; Rahman, Sudarman (Sasambo Journal of Pharmacy, 2025)
Free radicals are molecules with unpaired electrons that are reactive and unstable. Gold nanoparticles (AuNPs) have an antioxidant reducing Au3+ to Au+ which can stabilize free radicals. This research aims to characterize AuNPs, formulate and evaluate AuNPs antiaging serum with sirih hutan leaves fraction and antioxidant activity test. The research method used was maceration, sirih hutan leaves were extracted using 96% ethanol, fractionation using n-hexane, biosynthesis of AuNPs, formulation, and antioxidant activity using the DPPH method. The data analysis used One Way Anova test and post hoc Tukey (CI 95%). The research results showed that ethanol extract and n-hexane fraction were obtained at 132.5059 g and 18.3804 g respectively. Biosynthesis characterization of AuNPs have a particle size of 424.9 nm. Formulation and evaluation of AuNPs formulation were generally obtained according to SNI. The antioxidant activity of the formulation and vitamin C showed that the percentage of DPPH increased with increasing concentration, IC50 values of the formulaion and vitamin C showed 35.21 Â± 0.95; 17.95 Â± 0.34 ppm respectively. Based on One Way Anova test, there was significant difference in each concentration in the percentage of DPPH (p<0.05). and the formulation and vitamin C were classified as very strong antioxidants (IC50<50).